2016
DOI: 10.1186/s13046-016-0363-6
|View full text |Cite
|
Sign up to set email alerts
|

RNF8 promotes epithelial-mesenchymal transition of breast cancer cells

Abstract: BackgroundEpithelial-mesenchymal transition (EMT) is a crucial step for solid tumor progression and plays an important role in cancer invasion and metastasis. RNF8 is an ubiquitin E3 ligase with RING domain, and plays essential roles in DNA damage response and cell cycle regulation. However the role of RNF8 in the pathogenesis of breast cancer is still unclear.MethodsThe expression of RNF8 was examined in different types of breast cell lines by Western Blotting. EMT associated markers were examined by Immunofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 40 publications
5
55
1
1
Order By: Relevance
“…EMT plays an important role in the differentiation of tissues and organs and in the formation of the body plan, as well as contributes to cancer progression and other diseases [21, 22]. In the current study, we found that Prrx2 may participate in the EMT process, which is supported by the following evidence.…”
Section: Discussionsupporting
confidence: 78%
“…EMT plays an important role in the differentiation of tissues and organs and in the formation of the body plan, as well as contributes to cancer progression and other diseases [21, 22]. In the current study, we found that Prrx2 may participate in the EMT process, which is supported by the following evidence.…”
Section: Discussionsupporting
confidence: 78%
“…RNF8 is a newly identified coactivator of ERα [10]. The expression of RNF8 was found to be higher in malignant breast cancer tissues compared with normal tissues and was strongly correlated to lymph node metastases and poor survival [82]. The increased level of RNF8 in breast cancer samples was positively correlated with ERα expression.…”
Section: Tumorigenesis and Cancer Progressionmentioning
confidence: 93%
“…The inhibition of GSK3β causes the accumulation and nuclear translocation of β-catenin, which activates EMT-related gene transcription [81]. Overexpression of RNF8 in MCF-7 cells promoted the phosphorylation of GSK3β and further inhibited the activity of GSK3β [82]. The phosphorylation of β-catenin decreased and its protein level increased in RNF8 overexpressed cells, while phosphorylated β-catenin increased and its expression decreased in RNF8 silenced cells.…”
Section: Tumorigenesis and Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study conducted by Shao and colleagues supports our findings by showing that RNF8 is upregulated in malignant breast cancer cells and that overexpressed RNF8 can promote EMT in cell-based experiments and a nude mouse xenograft model. 10 Although DSB-associated RNF8 was known to be a guardian of the genome, we have revealed a novel role for DSB-dissociated RNF8 in cancer metastasis and chemoresistance (Fig. 1).…”
mentioning
confidence: 83%